2021
DOI: 10.3390/biom11081068
|View full text |Cite
|
Sign up to set email alerts
|

Chronic DDE Exposure Modifies Mitochondrial Respiration during Differentiation of Human Adipose-Derived Mesenchymal Stem Cells into Mature Adipocytes

Abstract: The contribution of environmental pollutants to the obesity pandemic is still not yet fully recognized. Elucidating possible cellular and molecular mechanisms of their effects is of high importance. Our study aimed to evaluate the effect of chronic, 21-day-long, 2,2-bis (4-chlorophenyl)-1,1-dichlorethylenedichlorodiphenyldichloroethylene (p,p′-DDE) exposure of human adipose-derived mesenchymal stem cells committed to adipogenesis on mitochondrial oxygen consumption on days 4, 10, and 21. In addition, the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Adipose tissue plays an active role in the body's regulation of appetite and inflammatory responses. DDE can upregulate adipogenesis by stimulating adipogenic pathways that promote adipocyte hyperplasia [19,39]. Significant weight loss leads to an increase in plasma levels of adiponectin, a signaling peptide that regulates the metabolism of lipids and glucose, and a decrease in levels of leptin, a hormone involved in regulation of energy balance and appetite [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue plays an active role in the body's regulation of appetite and inflammatory responses. DDE can upregulate adipogenesis by stimulating adipogenic pathways that promote adipocyte hyperplasia [19,39]. Significant weight loss leads to an increase in plasma levels of adiponectin, a signaling peptide that regulates the metabolism of lipids and glucose, and a decrease in levels of leptin, a hormone involved in regulation of energy balance and appetite [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Breast-feeding is another important form of human exposure. A growing amount of epidemiological evidence, in both in vivo and in vitro studies, have associated persistent organic pollutants, such as DDT and the DDT metabolite p,p'-DDE, with obesity [90][91][92][93]. Acute exposure causes harm to the central nervous system, while chronic exposure can result in liver cancer, disruption of endocrine control, harm of the fetus and fertility, and increased risk of Type 2 diabetes.…”
Section: Organophosphate Pesticides (Opps)mentioning
confidence: 99%
“…If addition to their paracrine activity, ASCs mediate regeneration via direct differentiation if the organ or tissue affected by degeneration is mesodermal (e.g., bone, fat tissue or cartilage). In this context, Kladnicka et al [10] demonstrated that chronic exposure of ASCs to the environmental pollutant 2,2-bis (4-chlorophenyl)-1,1-dichlorethylenedichlorodiphenyldichloroethylene (p,p'-DDE) modifies mitochondrial respiration during adipogenic differentiation. Since this phenomenon could bias ASCs towards adipogenesis, these results provide a potential link between environmental pollutants produced during the Anthropocene epoch and the current obesity epidemic especially prevalent in developed and developing countries.…”
mentioning
confidence: 99%